Nivolumab in gastric cancer with liver metastasis complicated by immune-mediated hepatitis: a case report and FAERS database analysis - Zhang, Yong-Li; Zhao, Jia-Lan; Qu, Ke-Jun; Jiao, Zong-Lin; Chen, Yan-Ru; Zhou, Jia; Li, Jiang-Lin; Li, Jun-Wei (Frontiers in Immunology, 2025)
Nivolumab is a monoclonal antibody that targets the PD-1 pathway, significantly transforming cancer immunotherapy. However, its use is associated with immune-related adverse events (irAEs), including immune-mediated hepatitis (IMH), which can be severe or even life-threatening. We present a case of an 81-year-old male with gastric cancer and liver metastasis, who demonstrated significant anti-tumor efficacy following nivolumab monotherapy. The patient developed grade 3 IMH during treatment, but after discontinuing the medication and receiving timely treatment, his symptoms improved, and liver biochemical markers declined. Additionally, using the FDA Adverse Event Reporting System (FAERS) database, we analyzed the incidence of hepatitis adverse events caused by different immune checkpoint inhibitors (ICIs) in various age groups of patients to better understand the safety of these drugs in different patient populations.